EFEKTIFITAS LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SINEMA EDUKASI UNTUK MENINGKATKAN ACADEMIC HARDINESS SISWA KELAS KHUSUS OLAHRAGA - Dita Alinda Restiani; Sigit Hariyadi (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study aims to examine the effectiveness of group counseling services using educational cinema techniques in improving the academic hardiness of students in Special Sports Classes. The study used a quantitative approach with a quasi-experimental pretest-posttest control group design. The research subjects consisted of 24 students selected through purposive sampling and divided into experimental and control groups. Data collection used an academic hardiness scale based on Kobasa's theory (1982) with a Cronbach's Alpha reliability of 0.826. Data analysis used the Wilcoxon and N-Gain tests. The results showed a significant increase in the experimental group (Sig. 0.002 < 0.05) with a Moderate N-Gain score. The results indicate that group counseling services using educational cinema techniques are effective in improving students' academic hardiness.